Evaluation of CD24 and CD44 as cancer stem cell markers in squamous cell carcinoma and epithelial dysplasia of the oral cavity by q- RT-PCR - Majid Mirhashemi; Narges Ghazi; Nasrollah Saghravanian; Ali Taghipour; Farnaz Mohajertehran (Wolters Kluwer Medknow Publications, 2020)
Background: Squamous cell carcinoma (SCC) is the most common cancer of the oral cavity and may be preceded by dysplastic epithelial lesion. Oral SCC (OSCC) contains a rare subset of cancer cells with self-renewal ability, termed as cancer stem cells (CSCs). CD24 and CD44 as CSC markers are cell surface glycoproteins. These markers contribute to the onset, maintenance, and extension of tumor growth, as well as angiogenesis. In the present study, these two markers were simultaneously evaluated to provide a specific phenotype for carcinogenesis process in oral cavity. Materials and Methods: In this analytical-cross-sectional study, the expression of CD24 and CD44 genes was evaluated in 45 OSCCs (20 low-grade and 25 high-grade) and 15 oral epithelial dysplasia specimens by real-time quantitative reverse transcription polymerase chain reaction. Kruskal-Wallis and Mann-Whitney U-test, Kendall, and Spearman tests were used for statistical analysis. The significance level was considered <0.05. Results: High expression of both markers genes was reported in two-thirds of samples. There was no significant difference between studied groups in gene expression of CD24 and CD44 whereas statistically significant association between CD24 and CD44 was observed in all three groups. This correlation was more significant in OSCC groups (P < 0.001). Conclusion: High expression of CSC markers in OSCC and oral epithelial dysplasia revealed the importance of accurate examination of dysplastic lesions with high expression of these markers and the possibility of malignant transformation. Regarding a significant association of two markers, further studies are necessary to provide a specific phenotype (CD44 high CD24 high) for these lesions.